Second-order Talbot effect with entangled photon pairs - Luo, Kai Hong; Wen, Jianming; Chen, Xi-Hao; Liu, Qian; Xiao, Min; Wu, Ling-An (Physical Review A)

Lensless ghost imaging with true thermal light - Chen, Xi-Hao; Liu, Qian; Luo, Kai Hong; Wu, Ling-An (Optics Letters)

Fundstück: Eine Suffragette im ersten Weltkrieg: Ethel Smyths March of the Women und das King Albert’s Book - Grotjahn, Rebecca (Blickwechsel Ost - West. Gender-Topographien)

Convolution algebras for multivariable Bessel functions - Rösler, Margit (Infinite Dimensional Harmonic Analysis IV)

Das communityorientierte Vorgehen der "Settlerinnen" von "Hull-House": Soziales Kapital und Perspektiven auf die Professionalisierung Sozialer Arbeit - Landhäußer, Sandra (Disziplingeschichte der Erziehungswissenschaft als Geschlechtergeschichte)
Der gegenwärtig verstärkt formulierte Anspruch, dass sich Soziale Arbeit am lokalen Sozialraum ihrer AdressatInnen auszurichten hat, wird in dem vorlie- genden Aufsatz aus einer historischen Perspektive in den Blick genommen. Sowohl die aktuellen Vorgehensweisen im Rahmen einer sozialräumlich aus- gerichteten Sozialen Arbeit als auch die Tätigkeiten der ‚Settlerinnen‘ des Settlements ‚Hull-House‘, das 1889 in Chicago gegründet wurde, lassen sich mit der analytischen Kategorie des sozialen Kapitals und seiner Aktivierung grundlegend analysieren. Dabei werden Unterschiede und Gemeinsamkeiten zwischen den Ansätzen deutlich, die Anlass für eine Diskussion über aktuell eingesetzte communityorientierte Strategien liefern.
Keywords: Pragmatismus; Sozialkapital; Hull-House; Communityorientierung; Settlerinnen

Liquid Crystal Nano-particles, LCNANOP – a SONS II Collaborative Research Project - Goodby, J. W.; Bates, M.; Saez, I. M.; Gorecka, E.; Kitzerow, Heinz-Siegfried; Guillon, D.; Donnio, B.; Serrano, J.-L.; Deschenaux, R. (Mater. Res. Soc. Symp. Proc. 1134)

On ICA of improper and noncircular sources - Schreier, Peter J.; Adali, Tülay; Scharf, Louis L. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
We provide a review of independent component analysis (ICA) for complex-valued improper and noncircular random sources. An improper random signal is correlated with its complex conjugate, and a noncircular random signal has a rotationally variant probability distribution. We present methods for ICA using second-order statistics, and higher-order statistics. For ICA based on second-order statistics, we emphasize the key role played by the circularity coefficients, which are the canonical correlations between the source and the complex conjugate. For ICA based on higher-order statistics, we show how to extend algorithms for real-valued ICA to the complex domain using Wirtinger calculus.

Gabor discretization of the Weyl product for modulation spaces and filtering of nonstationary stochastic processes - Wahlberg, Patrik; Schreier, Peter J. (Appl.\ Comput.\ Harmon.\ Anal.)

Superposition coded modulation and iterative linear MMSE detection - Ping, Li; Tong, Jun; Yuan, Xiaojun; Guo, Qinghua (IEEE J.\ Select.\ Areas Comm.)

Superposition coded modulation with peak-power limitation - Tong, Jun; Ping, Li; Ma, Xiao (IEEE Trans.\ Inform.\ Theory)

Coherent Fusion of Information for Optimal Detection in Sensor Networks - Ramírez, D.; Vía, J.; Santamaría, I. (Proc.\ IEEE Work.\ Stat.\ Signal Process.)

Entropy and Kullback-Leibler divergence estimation based on Szegö’s Theorem - Ramírez, D.; Vía, J.; Santamaría, I.; Crespo, P. (Proc.\ Eur.\ Signal Process.\ Conf.)

The Wiener filter for locally stationary stochastic processes is rarely locally stationary - Wahlberg, Patrik; Schreier, Peter J. (Proc. 17th\ European Signal Process.\ Conf.)

Berührungslose Materialfeuchtemessung nach dem NIR-Prinzip bei schnell variierendem Messgutabstand - Wetzlar, Dietmar; Krumme, Matthias (4. CMM-Workshop Innovative Feuchtemessung in Forschung und Praxis)

Rezension von Martina Heßler (2007): Die kreative Stadt. Zur Neuerfindung eines Topos - Alpsancar, Suzana (Archiv für Sozialgeschichte)

Bewegte Situationen – Schlüsselprobleme ausgesuchter Beobachtungsverfahren - Haller, Melanie (In: Leipziger Sportwissenschaftlichen Beiträge Band 50/2009 Qualitative Forschungsansätze in der Sportwissenschaft, S. 82-97 (zusammen mit Tim Bindel, Thomas Pille & Bernd Schulze))

Körpererfahrung und Naturglaube. Subjektivierungsstrategien in der Tangokultur - Haller, Melanie; Klein (Hg.), Gabriele (Tango in Translation. Tanz zwischen Medien, Kulturen, Kunst und Politik, transcript: Bielefeld, S. 123-138 (zusammen mit Gabriele Klein))

Verschmelzung: Bürgerliches Paarideal im Tango Argentino - Haller, Melanie; Klein (Hg.), Gabriele (Tango in Translation. Tanz zwischen Medien, Kulturen, Kunst und Politik, Bielefeld 2009, S. 89-103)

Bewegte Ordnungen: Kontingenz und Intersubjektivität im Tango Argentino - Haller, Melanie; Alkemeyer, Thomas; Brümmer, Kristina; Kodalle, Rea; Pille (Hg.), Thomas (Ordnung in Bewegung. Choreographien des Sozialen. Körper in Sport, Tanz, Arbeit und Bildung, Bielefeld, S. 91-105)

Versinkt die Kapitalmarkttheorie in logischen Widersprüchen, oder: Ist arqus e.V. aus dem Schneider? - Blaufus, Kay; Hundsdoerfer, Jochen; Kiesewetter, Dirk; König, Rolf J.; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Niemann, Rainer; Schanz, Deborah; Sureth-Sloane, Caren; Treisch, Corinna (Schmalenbachs Zeitschrift für betriebswirtschaftliche Forschung)

Alkoxide Clusters in Solution: An EXAFS Study of the Example Y(OEtOMe)3 and the Degradation Induced by Structural Modifiers - Bauer, Matthias; Bertagnolli, Helmut (Zeitschrift für Physikalische Chemie)
Abstract Yttrium methoxyethoxide Y(OEtOMe) 3 is an important precursor for the sol-gel preparation of Y 2 O 3 -containing materials. Its aggregation degree and the clusters, formed in solution of 2-methoxyethanol and modified by the ligands Hacac, i PrOH and THF are studied by means of EXAFS spectroscopy. The cluster geometries of the formed complexes deviate from the well-known cyclic decameric structure of the crystalline solid Y(OEtOMe) 3 . A pentanuclear square-pyramidal framework, which was found for Y(OEtOMe) 3 , dissolved in 2-methoxyethanol in a previous study, is confirmed by a detailed discussion of the structural EXAFS parameters. While the addition of the Lewis bases i PrOH and THF does not change the aggregation degree and short range order of Y(OEtOMe) 3 in solution, chelating Hacac causes a stepwise degradation of the original pentameric metal framework. Details of the degradation pathway as deduced from the EXAFS results are given, which could not be achieved by any other spectroscopic method so far. The yttrium coordination number and third cumulants, which are necessary to account for asymmetry in the individual shells, are used in order to identify structural changes of the samples in comparison with the initially formed Y 5 -complex.
Keywords: Physical and Theoretical Chemistry

Syntheses, Crystal Structures, Spectroscopic Properties, and Catalytic Aerobic Oxidations of Novel Trinuclear Non‐Heme Iron Complexes - Rabe, Volker; Frey, Wolfgang; Baro, Angelika; Laschat, Sabine; Bauer, Matthias; Bertagnolli, Helmut; Rajagopalan, Subramanian; Asthalter, Tanja; Roduner, Emil; Dilger, Herbert; Glaser, Thorsten; Schnieders, David (European Journal of Inorganic Chemistry)
Keywords: Inorganic Chemistry

A zirconium methacrylate oxocluster as precursor for the low-temperature synthesis of porous zirconium(iv) dicarboxylates - Guillerm, Vincent; Gross, Silvia; Serre, Christian; Devic, Thomas; Bauer, Matthias; Férey, Gérard (Chem. Commun.)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Functional Chromium Wheel-Based Hybrid Organic-Inorganic Materials for Dielectric Applications - Di Noto, Vito; Boeer, Angelika B.; Lavina, Sandra; Muryn, Christopher A.; Bauer, Matthias; Timco, Grigore A.; Negro, Enrico; Rancan, Marzio; Winpenny, Richard E. P.; Gross, Silvia (Advanced Functional Materials)
Keywords: Electrochemistry; Condensed Matter Physics; Biomaterials; Electronic; Optical and Magnetic Materials

Towards X-Ray Absorption Spectroscopy in Real Time - Bauer, Matthias; Bertagnolli, Helmut (ChemPhysChem)
Keywords: Physical and Theoretical Chemistry; Atomic and Molecular Physics; and Optics

A Computational Model of Acoustic Packaging - Schillingmann, Lars; Wrede, Britta; Rohlfing, Katharina (IEEE Transactions on Autonomous Mental Development)
In order to learn and interact with humans, robots need to understand actions and make use of language in social interactions. The use of language for the learning of actions has been emphasized by Hirsh-Pasek and Golinkoff (MIT Press, 1996), introducing the idea of acoustic packaging. Accordingly, it has been suggested that acoustic information, typically in the form of narration, overlaps with action sequences and provides infants with a bottom-up guide to attend to relevant parts and to find structure within them. In this article, we present a computational model of the multimodal interplay of action and language in tutoring situations. For our purpose, we understand events as temporal intervals, which have to be segmented in both, the visual and the acoustic modality. Our acoustic packaging algorithm merges the segments from both modalities based on temporal overlap. First evaluation results show that acoustic packaging can provide a meaningful segmentation of action demonstration within tutoring behavior. We discuss our findings with regard to a meaningful action segmentation. Based on our future vision of acoustic packaging we point out a roadmap describing the further development of acoustic packaging and interactive scenarios it is employed in.

On the loop of action modification and the recipient's gaze in adult-child interaction - Pitsch, Karola; Vollmer, Anna-Lisa; Fritsch, Jannik; Wrede, Britta; Rohlfing, Katharina; Sagerer, Gerhard (Gesture and Speech in Interaction)
Learning is a social endeavor, in which the learner generally receives support from his/her social partner(s). In developmental research – even though tutors/adults behavior modifications in their speech, gestures and motions have been extensively studied, studies barely consider the recipient’s (i.e. the child’s) perspective in the analysis of the adult’s presentation, In addition, the variability in parental behavior, i.e. the fact that not every parent modifies her/his behavior in the same way, found less fine-grained analysis. In contrast, in this paper, we assume an interactional perspective investigating the loop between the tutor’s and the learner’s actions. With this approach, we aim both at discovering the levels and features of variability and at achieving a better understanding of how they come about within the course of the interaction. For our analysis, we used a combination of (1) qualitative investigation derived from ethnomethodological Conversation Analysis (CA), (2) semi-automatic computational 2D hand tracking and (3) a mathematically based visualization of the data. Our analysis reveals that tutors not only shape their demonstrations differently with regard to the intended recipient per se (adult-directed vs. child-directed), but most importantly that the learner’s feedback during the presentation is consequential for the concrete ways in which the presentation is carried out.
Keywords: gaze; gesture; Multimodal; adult-child interaction

Computational Analysis of Motionese Toward Scaffolding Robot Action Learning - Nagai, Yukie; Rohlfing, Katharina (IEEE Transactions on Autonomous Mental Development)
A difficulty in robot action learning is that robots do not know where to attend when observing action demonstration. Inspired by human parent-infant interaction, we suggest that parental action demonstration to infants, called motionese, can scaffold robot learning as well as infants. Since infants knowledge about the context is limited, which is comparable to robots, parents are supposed to properly guide their attention by emphasizing the important aspects of the action. Our analysis employing a bottom-up attention model revealed that motionese has the effects of highlighting the initial and final states of the action, indicating significant state changes in it, and underlining the properties of objects used in the action. Suppression and addition of parents body movement and their frequent social signals to infants produced these effects. Our findings are discussed toward designing robots that can take advantage of parental teaching.

Improving HRI design by applying Systemic Interaction Analysis (SInA) - Lohse, Manja; Hanheide, Marc; Pitsch, Karola; Rohlfing, Katharina; Sagerer, Gerhard (Interaction Studies (Special Issue: Robots in the Wild: Exploring HRI in naturalistic environments))

Analysing the effect of contingency in tutoring situations - Lohan, Katrin Solveig; Rohlfing, Katharina; Wrede, Britta
In developmental research, tutoring behavior has been identified as scaffolding infants’ learning processes. It has been defined in terms of child-directed speech (Motherese), child-directed motion (Motionese), and contingency. Contingency describes situations in which two agents socially interact with each other and Csibra and Gergely showed that contingency is a char- acteristic aspect of social interaction [3]. In the field of developmental robotics, research often assumes that in human-robot interaction (HRI), robots are treated similar to infants, because their immature cognitive capabilities benefit from this behavior. Here we present results con- cerning the acceptance of a robotic agent in a social learning scenario obtained via comparison to adults and 8-11 months old infants in equal conditions. These results constitute an important empirical basis for making use of tutoring behavior in social robotics. Our results reveal significant differences between Adult-Child Interaction (ACI), Adult-Adult Interaction (AAI) and Adult-Robot Interaction (ARI) in eye gaze behavior suggesting that contingency is impaired in the analyzed ARI situation.
Keywords: Eyegaze; tutoring situations; Contingency

Towards Learning by Interacting - Wrede, Britta; Rohlfing, Katharina; Hanheide, Marc; Sagerer, Gerhard (Creating Brain-Like Intelligence: From Basic Principles to Complex Intelligent Systems)

People modify their tutoring behavior in robot-directed interaction for action learning - Vollmer, Anna-Lisa; Lohan, Katrin Solveig; Fischer, Kerstin; Nagai, Yukie; Pitsch, Karola; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (Development and Learning, 2009. ICDL 2009. IEEE 8th International Conference on Development and Learning)
In developmental research, tutoring behavior has been identified as scaffolding infants' learning processes. It has been defined in terms of child-directed speech (Motherese), child-directed motion (Motionese), and contingency. In the field of developmental robotics, research often assumes that in human-robot interaction (HRI), robots are treated similar to infants, because their immature cognitive capabilities benefit from this behavior. However, according to our knowledge, it has barely been studied whether this is true and how exactly humans alter their behavior towards a robotic interaction partner. In this paper, we present results concerning the acceptance of a robotic agent in a social learning scenario obtained via comparison to adults and 8-11 months old infants in equal conditions. These results constitute an important empirical basis for making use of tutoring behavior in social robotics. In our study, we performed a detailed multimodal analysis of HRI in a tutoring situation using the example of a robot simulation equipped with a bottom-up saliency-based attention model. Our results reveal significant differences in hand movement velocity, motion pauses, range of motion, and eye gaze suggesting that for example adults decrease their hand movement velocity in an Adult-Child Interaction (ACI), opposed to an Adult-Adult Interaction (AAI) and this decrease is even higher in the Adult-Robot Interaction (ARI). We also found important differences between ACI and ARI in how the behavior is modified over time as the interaction unfolds. These findings indicate the necessity of integrating top-down feedback structures into a bottom-up system for robots to be fully accepted as interaction partners.
Keywords: robot simulation; hand movement velocity; robotic interaction partner; robotic agent; robot-directed interaction; multimodal analysis; Motionese; Motherese; intelligent tutoring systems; immature cognitive capability; human computer interaction; eye gaze; child-directed speech; child-directed motion; bottom-up system; bottom-up saliency-based attention model; adult-robot interaction; adult-child interaction; adult-adult interaction; human-robot interaction; action learning; social learning scenario; social robotics; software agents; top-down feedback structures; tutoring behavior

Differential phase compensated constant modulus algorithm for phase noise tolerant coherent optical transmission - El-Darawy, Mohamed; Pfau, Timo; Hoffmann, Sebastian; Noé, Reinhold (2009 IEEE/LEOS Summer Topical Meeting)

Frühe Hilfen rechnen sich - Wagenknecht, Inga; Meier-Gräwe, Uta; Fegert, Jörg M. (Frühförderung interdisziplinär)

Tagungsbericht: 122. Jahresversammlung des Vereins für niederdeutsche Sprachforschung in Ratzeburg. - Wallmeier, Nadine; Menke, Kirsten (Korrespondenzblatt des Vereins für niederdeutsche Sprachforschung)

Deutsche Frauen, deutscher Sang – Nation, Gender und die idea of serious music - Grotjahn, Rebecca (Deutsche Frauen, deutscher Sang – Musik in der deutschen Kulturnation)

Einleitung - Grotjahn, Rebecca (Deutsche Frauen, deutscher Sang – Musik in der deutschen Kulturnation)

Deutsche Frauen, deutscher Sang – Musik in der deutschen Kulturnation

Communityorientierung in der Sozialen Arbeit: Die Aktivierung von sozialem Kapital - Landhäußer, Sandra
Die Orientierung am Sozialraum - an den lokalen sozialen Räumen von AkteurInnen - hat in der Sozialen Arbeit eine lange Tradition und erfährt zunehmende, auch öffentliche Aufmerksamkeit. An den Beispielen der Settlementarbeit, der Gemeinwesenarbeit und der sozialraumorientierten Sozialen Arbeit werden in diesem Band zentrale historische Entwicklungen der Communityorientierung in der Sozialen Arbeit rekonstruiert. Die zugrunde liegende Programmatik wird anschließend mit empirischen Daten konfrontiert und systematisch in aktuelle gesellschaftliche Zusammenhänge
Keywords: Community Gemeinwesenarbeit Settlementarbeit Soziale Arbeit Soziales Kapital

Continuous-variable quantum information processing - Andersen, U.L.; Leuchs, G.; Silberhorn, Christine (Laser & Photonics Reviews)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Welt der Technik – technische Welt? - Alpsancar, Suzana; Blanke, Ulf; Nowak, Frauke (Technikfolgenabschätzung – Theorie und Praxis)

Der Einfluss von Internationalisierung, Vermögens- und Kapitalstruktur auf die Konzernsteuerquote im Branchenvergleich - eine empirische Analyse - Sureth-Sloane, Caren; Halberstadt, Alexander; Bischoff, Dennis (Steuer und Wirtschaft)

Income Tax Analysis: A Comparison of Microsimulation versus Group Simulation - Müller, Heiko; Sureth-Sloane, Caren (International Journal of Microsimulation)

Entwicklung und psychometrische Überprüfung eines Messinstruments zur Erfassung pädagogischer Kompetenzen in der universitären Lehrerbildung. - Seifert, Andreas; Hilligus, Annegret Helen; Schaper, Niclas (Lehrerbildung auf dem Prüfstand)

Which ostensive stimuli can be used for a robot to detect and maintain tutoring situations? - Lohan, Katrin Solveig; Vollmer, Anna-Lisa; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (IEEE International Workshop on Social Signal Processing)
In developmental research, tutoring behavior has been identified as scaffolding infants’ learning processes. Infants seem sensitive to tutoring situations and they detect these by ostensive cues [4]. Some social signals such as eye-gaze, child-directed speech (Motherese), child-directed motion (Motionese), and contingency have been shown to serve as ostensive cues. The concept of contingency describes exchanges in which two agents interact with each other reciprocally. Csibra and Gergely argued that contingency is a characteristic ostensive stimulus of a tutoring situation [4]. In order for a robot to be treated similar to an infant, it has to both, be sensitive to the ostensive stimuli on the one hand and induce tutoring behavior by its feedback about its capabilities on the other hand. In this paper, we raise the question whether a robot can be treated similar to an infant in an interaction. We present results concerning the acceptance of a robotic agent in a social learning scenario, which we obtained via comparison to interactions with 8-11 months old infants and adults in equal conditions. We applied measurements for motion modifications (Motionese) and eye-gaze behavior. Our results reveal significant differences between Adult-Child Interaction (ACI), Adult-Adult Interaction (AAI) and Adult- Robot Interaction (ARI) suggesting that in ARI, robotdirected tutoring behavior is even more accentuated in terms of Motionese, but contingent responsivity is impaired. Our results confirm previous findings [14] concerning the differences between ACI, AAI, and ARI and constitute an important empirical basis for making use of ostensive stimuli as social signals for tutoring behavior in social robotics.
Keywords: Ostensive Signals; Contingency; Motionese; hri

Attention via synchrony. Making use of multimodal cues in social learning - Rolf, Matthias; Hanheide, Marc; Rohlfing, Katharina (IEEE Transactions on Autonomous Mental Development)
Infants learning about their environment are confronted with many stimuli of different modalities. Therefore, a crucial problem is how to discover which stimuli are related, for instance, in learning words. In making these multimodal "bindings," infants depend on social interaction with a caregiver to guide their attention towards relevant stimuli. The caregiver might, for example, visually highlight an object by shaking it while vocalizing the object's name. These cues are known to help structuring the continuous stream of stimuli. To detect and exploit them, we propose a model of bottom-up attention by multimodal signal-level synchrony. We focus on the guidance of visual attention from audio-visual synchrony informed by recent adult-infant interaction studies. Consequently, we demonstrate that our model is receptive to parental cues during child-directed tutoring. The findings discussed in this paper are consistent with recent results from developmental psychology but for the first time are obtained employing an objective, computational model. The presence of " multimodal motherese" is verified directly on the audio-visual signal. Lastly, we hypothesize how our computational model facilitates tutoring interaction and discuss its application in interactive learning scenarios, enabling social robots to benefit from adult-like tutoring. Document Type: Article

Gesture as a support for word learning: The case of under - McGregor, Karla K.; Rohlfing, Katharina; Bean, Allison; Marschner, Ellen (JOURNAL OF CHILD LANGUAGE)
Forty children, aged 1;8-2;0, participated in one of three training conditions meant to enhance their comprehension of the spatial term under: the +Gesture group viewed a symbolic gesture for under during training; those in the +Photo group viewed a still photograph of objects in the under relationship; those in the Model Only group did not receive supplemental symbolic support. Children's knowledge of under was measured before, immediately after, and two to three days after training. A gesture advantage was revealed when the gains exhibited by the groups on untrained materials (but not trained materials) were compared at delayed post-test (but not immediate Post-test). Gestured input promoted more robust knowledge of the meaning of under, knowledge that was less tied to contextual familiarity and more prone to consolidation. Gestured input likely reduced cognitive load while emphasizing both the location and the movement relevant to the meaning of under.

Socio-pragmatics and attention: Contributions to gesturally guided word learning in toddlers - Booth, A. E; McGregor, Karla K.; Rohlfing, Katharina (Journal of Language Learning and Development)

Towards a Computational Model of Acoustic Packaging - Schillingmann, Lars; Wrede, Britta; Rohlfing, Katharina (International Conference on Development and Learning (ICDL 2009))
Keywords: Acoustic Packaging; multimodal

The Structure of Robot-Directed Interaction compared to Adult- and Infant-Directed Interaction using a Model for Acoustic Packaging - Schillingmann, Lars; Wrede, Britta; Rohlfing, Katharina; Fischer, Kerstin (Spoken Dialogue and Human-Robot Interaction)

Systemic interaction analysis (SInA) in HRI - Lohse, Manja; Hanheide, Marc; Rohlfing, Katharina; Sagerer, Gerhard (Proceedings of the 4th ACM/IEEE international conference on Human robot interaction - HRI '09)
Keywords: SINA; human robot interaction; biron

Which Motionese Parameters Change with Children’s Age? - Vollmer, Anna-Lisa; Lohan, Katrin Solveig; Fritsch, Jannik; Wrede, Britta; Rohlfing, Katharina
Keywords: Contingency; Motionese

Acoustic Packaging - Schillingmann, Lars; Wrede, Britta; Rohlfing, Katharina (HUROBINT2009)

LEK – Längsschnittliche Erhebung pädagogischer Kompetenzen von Lehramtsstudierenden: Testinstrumente, Forschungsdesign und Fragestellungen. - König, Johannes; Seifert, Andreas; Blömeke, Sigrid; Schaper, Niclas (AEPF-Tagung „Selbstregulation – Fremdregulation“)

Welche Dimensionen bzw. Modellstruktur liegt der Messung pädagogischer Kompetenz in der universitären Lehrerausbildung zugrunde? - Seifert, Andreas; Schaper, Niclas (AEPF-KBBB-Tagung)

Tanzeinlagen im Sprechtheater des 19. Jahrhundert - Tumat, Antje (Tanz im Musiktheater – Tanz als Musiktheater: Bericht eines internationalen Symposions über Beziehungen von Tanz und Musik im Theater)

London: Schauspielmusik und Maskenspiele - Tumat, Antje (Händels Opern. Teilband 1)

Dose-dependent melanonychia by mitoxantrone. - Reinsberger, Claus; Meuth, SG; Wiendl, H (Mult Scler)

Die Spezifische Sprachentwicklungsstörung und daraus resultierende Folgeprobleme. - Grosser, Christine

Rapid Room-Temperature Synthesis and Characterization of Nanocrystals of a Prototypical Zeolitic Imidazolate Framework - Cravillon, Janosch; Münzer, Simon; Lohmeier, Sven-Jare; Feldhoff, Armin; Huber, Klaus; Wiebcke, Michael (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Nanocrystals of [Cu3(btc)2] (HKUST-1): a combined time-resolved light scattering and scanning electron microscopy study - Zacher, Denise; Liu, Jianing; Huber, Klaus; Fischer, Roland A. (Chemical Communications)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Formation of Ca2+-Induced Intermediate Necklace Structures of Polyacrylate Chains - Lages, Sebastian; Lindner, Peter; Sinha, Prashant; Kiriy, Anton; Stamm, Manfred; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

On global effects caused by locally noneffective unitary operations - Gharibian, Sevag; Kampermann, Hermann; Bruß, Dagmar (Quantum Information & Computation)
Given a bipartite quantum state rho with subsystems A and B of arbitrary dimensions, we study the entanglement detecting capabilities of locally noneffective, or cyclic, unitary operations [L. B. Fu, Europhys. Lett., vol. 75, pp. 1-7, 2006]. Local cyclic unitaries have the special property that they leave their target subsystem invariant. We investigate the distance between rho and the global state after local application of such unitaries as a possible indicator of entanglement. To this end, we derive and discuss closed formulae for the maximal such distance achievable for three cases of interest: (pseudo)pure quantum states, Werner states, and two-qubit states. What makes this criterion interesting, as we show here, is that it surprisingly displays behavior similar to recent anomalies observed for non-locality measures in higher dimensions, as well as demonstrates an equivalence to the CHSH inequality for certain classes of two-qubit states. Yet, despite these similarities, the criterion is not itself a non-locality measure. We also consider entanglement detection in bound entangled states.

Signatures of nonclassicality in mixed-state quantum computation - Datta, Animesh; Gharibian, Sevag (Physical Review A)
We investigate signatures of non-classicality in quantum states, in particular, those involved in the DQC1 model of mixed-state quantum computation [Phys. Rev. Lett. 81, 5672 (1998)]. To do so, we consider two known non-classicality criteria. The first quantifies disturbance of a quantum state under locally noneffective unitary operations (LNU), which are local unitaries acting invariantly on a subsystem. The second quantifies measurement induced disturbance (MID) in the eigenbasis of the reduced density matrices. We study the role of both figures of non-classicality in the exponential speedup of the DQC1 model and compare them vis-a-vis the interpretation provided in terms of quantum discord. In particular, we prove that a non-zero quantum discord implies a non-zero shift under LNUs. We also use the MID measure to study the locking of classical correlations [Phys. Rev. Lett. 92, 067902 (2004)] using two mutually unbiased bases (MUB). We find the MID measure to exactly correspond to the number of locked bits of correlation. For three or more MUBs, it predicts the possibility of superior locking effects.

Factoring polynomials over global fields - Belabas, Karim; van Hoeij, Mark; Klüners, Jürgen; Steel, Allan (Journal de Théorie des Nombres de Bordeaux)
We prove that van Hoeij’s original algorithm to factor univariate polynomials over the rationals runs in polynomial time, as well as natural variants. In particular, our approach also yields polynomial time complexity results for bivariate polynomials over a finite field.
Keywords: Algebra and Number Theory

The van Hoeij Algorithm for Factoring Polynomials - Klüners, Jürgen (The LLL Algorithm)
In this survey, we report about a new algorithm for factoring polynomials due to Mark van Hoeij. The main idea is that the combinatorial problem that occurs in the Zassenhaus algorithm is reduced to a very special knapsack problem. In case of rational polynomials, this knapsack problem can be very efficiently solved by the LLL algorithm. This gives a polynomial time algorithm, which also works very well in practice.

Social Networking Sites and the Surveillance Society. A Critical Case Study of the Usage of studiVZ, Facebook, and MySpace by Students in Salzburg in the Context of Electronic Surveillance - Fuchs, Christian

Practical Civil Virtues in Cyberspace: Towards the Utopian Identity of Civitas and Multitudo. Munich Series in Design Science (Münchener Schriften zur Design Science) - Fuchs, Christian; E. Zimmermann, Rainer

Some Reflections on Manuel Castells’ Book “Communication Power“ - Fuchs, Christian (tripleC (Cognition, Communication, Co-operation) – Open Access Journal for a Global Sustainable Information Society)

A fenntartható információs társadalom ideológiai tájképe. 2. rész (Sustainable Information Society as Ideology. Second Part, in Hungarian) - Fuchs, Christian (Információs Társadalom (Information Society))

A fenntartható információs társadalom ideológiai tájképe. 1. rész (Sustainable Information Society as Ideology. First Part, in Hungarian) - Fuchs, Christian (Információs Társadalom (Information Society))

Some Theoretical Foundations of Critical Media Studies: reflections on Karl Marx and the media - Fuchs, Christian (International Journal of Communication 3 (2009))

The role of income inequality in a multivariate cross- national analysis of the digital divide - Fuchs, Christian (Social Science Computer Review)

Cyberethics and Co- operation in the Information Society - Fuchs, Christian; Bichler, Robert; Raffl, Celina (Science and Engineering Ethics)

A Contribution to Theoretical Foundations of Critical Media and Communication Studies - Fuchs, Christian (Javnost-The Public)

Internet und Gesellschaft: Beiträge zu einer kritischen Theorie des Informationszeitalters [Internet and Society: Contibutions to a Critical Theory of the Information Age] - Fuchs, Christian (Neue Medien und kulturelle Vielfalt [New Media and Cultural Diversity])

Grundlagen der Kritik der Politischen Ökonomie der Medien [Foundations of the critique of the political economy of the media] - Fuchs, Christian (Bruchstücke: Kritische Ansätze zu Politik und Ökonomie im globalisierten Kapitalismus)

Towards a Critical Theory of Information - Fuchs, Christian (tripleC (cognition, communication, co-operation): Journal for a Global Sustainable Information Society)

Autopoiesis and Critical Social Systems Theory - Fuchs, Christian; Hofkirchner, Wolfgang (Autopoiesis in Organization Theory and Practice)

Kapitalistische Medien und kapitalistische Krise [Capitalist media and capitalist crisis] - Fuchs, Christian (Kapitalismus am Ende? [The end of capitalism?])

Conference Report: The Internet as Playground and Factory (November 12-14, 2009, The New School, New York City, USA) - Fuchs, Christian (tripleC)

Ordered Mesoporous In2O3: Synthesis by Structure Replication and Application as a Methane Gas Sensor - Waitz, Thomas; Wagner, Thorsten; Sauerwald, Tilman; Kohl, Claus-Dieter; Tiemann, Michael (Advanced Functional Materials)
The synthesis and characterization of ordered mesoporous In2O3 materials by structure replication from hexagonal mesoporous SBA-15 silica and cubic KIT-6 silica is presented. Variation of the synthesis parameters allows for different pore sizes and pore wall thicknesses in the products. The In2O3 samples turn out to be stable up to temperatures between 450 °C and 650 °C; such high thermal stability is necessary for their application as gas sensors. Test measurements show a high sensitivity to methane gas in concentrations relevant for explosion prevention. The sensitivity is shown to be correlated not only with the surface-to-volume ratio, but also with the nanoscopic structural properties of the materials.

Time-resolved photoluminescence study of mesoporous ZnO nanostructures - Schwalm, Michael; Horst, Swantje; Chernikov, Alexej; Rühle, Wolfgang W.; Lautenschläger, Stephan; Klar, Peter J.; Meyer, Bruno K.; Waitz, Thomas; Tiemann, Michael; Chatterjee, Sangam (physica status solidi (c))
We report a systematic study of the photoluminescence properties of ZnO nanostructures. In particular, mesoporous ZnO powders of varying surface-to-mass ratio are investigated and compared to a bulk reference. At low temperatures the emission from higher-energy states is very pronounced and even dominant for samples with high surface-to-mass ratio.

Social Networking Sites and the Surveillance Society - Allmer, Thomas; Sandoval, Marisol (American Philosophical Association Newsletter on Philosophy and Computers)

Morals in the world-picture - Matzner, Tobias (Sprache und Welt: Beiträge des 32. Internationalen Wittgenstein Symposiums)

Learning Parametrised RoboCup Rescue Agent Behaviour Using an Evolutionary Algorithm - Kruse, Michael; Baumann, Michael; Knieper, Tobias; Seipel, Christoph; Khaluf, Lial; Lehmann, Nico; Lermontow, Alex; Messinger, Christian; Richter, Simon; Schmidt, Thomas; Swars, Daniel

Coupling Dynamics of Quantum Dots in a Liquid-Crystal-Tunable Microdisk Resonator - Förstner, Jens; Meier, Cedrik; Piegdon, Karoline; Declair, Stefan; Hoischen, Andreas; Urbanski, Mark; Meier, Torsten; Kitzerow, Heinz-Siegfried (Advances in Optical Sciences Congress)
We experimentally and theoretically investigate microdisk resonators with embedded quantum dots immersed in a liquid crystal in its nematic phase, showing the tunabililty of the photonic modes via external parameters like temperature or electric field.
Keywords: tet_topic_microdisk

Konsumgesellschaft - Kleinschmidt, Christian (Sic et Non. Zeitschrift Philosophie / Kultur im Netz)

Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten

Schäfer, Friedrich August (1883-1958) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Foerster, Gotthilf Helmut (1895-1964) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Lehmbruck, Wilhelm (1881-1919) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Sehlbach, Erich (1898-1985) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Weigle, Maria (1893-1979) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Bunk, Gerard (1888-1958) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Heyne, Bodo (1893-1980) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Peters, Ilse - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Biblische Bilder - Beobachtungen zur Transformation der Bibel in der Klaviermusik in Deutschland im 19. und 20. Jahrhundert - Schroeter-Wittke, Harald (Inszenierungen der Heiligen Schrift. Jüdische und christliche Bibeltransformationen vom Mittelalter bis in die Moderne)

Ruhrgebietsperikopenreihe. Wir werden aber alle verwandelt werden (1 Kor 15,51b). Mit der Bibel durch RUHR 2010. Eine Perikopenreihe für das Ruhrgebiet - Schroeter-Wittke, Harald (Wir werden aber alle verwandelt werden. Handreichung zu den "Local Hero Wochen" in der Kulturhauptstadt RUHR 2010)

Heilige Scheu und profane Hygiene. Abendmahl als Zeichen der Nähe - Zwischen Scham und Verbundenheit - Schroeter-Wittke, Harald (Näher! 7 Wochen ohne Scheu. Arbeitshilfe zum Thema "Näher!")